FENOMENA PENGULANGAN KASUS KEKERASAN DALAM RUMAH TANGGA DI KELURAHAN PAL PUTIH KOTA SORONG - Nisa, Az-zahra Latifatun; Kurniwati, Aisyah Hafidah (Muadalah : Jurnal Hukum, 2024)
Acts of domestic violence are human rights violations and are crimes against human dignity and a form of discrimination that must be eliminated. These acts of violence often occur with various factors such as men who are always in power in the household, factors of socioeconomic conditions between the two parties that are unequal, household conditions that are very closed and so on. One aspect of domestic violence that is of particular concern is the repetition of violence. Therefore, appropriate and effective preventive efforts and interventions are needed to overcome this problem. Preventive efforts can be done through education and socialization about the importance of healthy relationships and avoiding acts of domestic violence. Meanwhile, intervention can be done through strict law enforcement against perpetrators of violence and providing support to victims in order to get out of adverse situations and get physical and psychological recovery.